The Role of Legal Anthropology in the field of Law - Habib Mustafa Ibrahim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Legal anthropology is a new science that dates back to the second half of the nineteenth century. This science is multidisciplinary because it studies laws and their role in society from both legal and anthropological perspectives. To this end, legal anthropology pays attention to social and cultural systems in society since, from the perspective of this discipline, social, cultural and legal conditions are influenced by each other. This paper aims to identify the role of legal anthropology in the field of law. The method used in this research is analytical, which is the most appropriate method to that highlight on the role of legal anthropology in the field of law. After a theoretical analysis, we came to the conclusion that because the law is a socio-cultural phenomenon, it should not be viewed only from the perspective of jurists, but attention must also be paid to social and cultural situations in legal anthropology. Research on both traditional and modern societies is the work of this science, so one of the obvious tasks of researchers is to explain the phenomenon of legal acculturation and legal pluralism in society.